Analisis Tingkat Kepuasan Pengguna Sistem Informasi Website AHU Menggunakan PIECES Framework - Dewi Puji Astuti; Elvin Leander Hadisaputro; Hasrullah Hasrullah (STMIK Budi Darma, 2022)
The use of information systems requires special arrangements and management, so this system is commonly referred to as a website information system. Website information system is a representation of information technology which is a medium in obtaining information. One of the benefits of a website-based information system is to facilitate the presentation of data that can be accessed by all internet users. The role of a website-based information system is to produce information for all levels of management. The need for information for a management process must be analyzed, so that the information produced can function and be right on target. One application of a website-based information system is a notarial information system. This study aims to evaluate user satisfaction of the Online AHU (General Legal Administration) Website in relation to the Directorate General of AHU. With the application of AHU Online as a breakthrough in public services by the Directorate General of AHU, these problems can be overcome as a form of excellent service to the community. In this case, it cannot be separated from the information system used in the company, of course it cannot be separated from the impressions of users (notary employees) in registering legal entities using the AHU Online Website. The method used is the PIECES Framework analysis method, which consists of several points of analysis, namely: Performance, Information and Data, Economics, Control and Security, Efficiency, and Service. The results of this study are an AHU website that is able to analyze the level of user satisfaction with the website information system using the PIECES Framework analysis method